Prognostic significance of tumor grade in early-stage endometrioid endometrial cancer - Akar, Serra; Harmankaya, Ismail; Celik, Cetin (Annals of Medical Research, 2021)
Aim: Although tumor grade has no impact on endometrial cancer stage, it carries prognostic and therapeutic importance. Surgical management and adjuvant treatment following surgery in certain patients depends on a number of factors including tumor grade. Although grade 3 tumors are included in the high-intermediate risk group, there are data demonstrating that there is a slight difference in survival between patients with grade 1 and 2 tumors in early-stage disease. In this study, we aimed to investigate the association of grade with clinicopathological characteristics, recurrence-free and disease-specific survival in patients treated at our clinic and diagnosed with endometrioid endometrial cancer. Material and Methods: 279 patients with early FIGO Stage endometrioid endometrial cancer treated between 2009-2018 in a University hospital were included in the study. The associations between tumor grade with stage, lymphovascular space invasion (LVSI), myometrial invasion, tumor size, and survival were analyzed.Results: LVSI, ≥50% myometrial invasion, advanced stage and > 2 cm tumor size were significantly higher in grade 3 tumors compared to patients with grade 1 tumors. Recurrence-free and disease-specific survival were significantly lower in patients with grade 2 and 3 tumors compared to patients with grade 1 tumors. In multivariate analysis of RFS and DSS, tumor grade, LVSI and stage were independent prognostic factors.Conclusion: According to this study, grade 2 tumors may not differ significantly from grade 3 tumors in terms of survival. Therefore, due to the potential adverse prognosis associated with grade 2 and 3 tumors, vigilance for recurrence is warranted.